2012
DOI: 10.2478/v10310-012-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides and PCBs in marine fish

Abstract: Organochlorine pesticides (such as 1,1,1-trichloro - 2,2 - bis (4-chlorophenyl) ethane (DDT) and its metabolites) and polychlorinated biphenyls (PCBs) are classified as Persistent Organic Pollutants (POPs) and are present in the contamination pattern of marine environments world-wide. Concentrations of PCBs and DDTs were measured in two marine species: garfish (Belone belone) and red mullet (Mullus barbatus). Samples were collected from Black Sea, Bulgaria during 2007 - 2010. The DDTs and PCBs were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
3
4
1
Order By: Relevance
“…DDT was also found in several fish samples except for horse mackerel in Turkey (Erdoğrul et al , 2005; Uluocak & Egemen, 2005; Erkmen & Kolankaya, 2006; Kalyoncu et al , 2009; Çakıroğulları & Secer, 2011; Bozcaarmutlu et al , 2014). OCP-concentrations in fish samples were dominated by total-DDT followed by total-HCH in this study, similar to the results found by Barlas et al (2000), Erdoğrul et al (2005), Coelhan et al (2006), Çakıroğulları & Secer (2011) and Georgieva et al (2012). This could be explained by the fact that DDT has high chemical and thermal stability (Di Bella et al ., 2006).…”
Section: Discussionsupporting
confidence: 91%
“…DDT was also found in several fish samples except for horse mackerel in Turkey (Erdoğrul et al , 2005; Uluocak & Egemen, 2005; Erkmen & Kolankaya, 2006; Kalyoncu et al , 2009; Çakıroğulları & Secer, 2011; Bozcaarmutlu et al , 2014). OCP-concentrations in fish samples were dominated by total-DDT followed by total-HCH in this study, similar to the results found by Barlas et al (2000), Erdoğrul et al (2005), Coelhan et al (2006), Çakıroğulları & Secer (2011) and Georgieva et al (2012). This could be explained by the fact that DDT has high chemical and thermal stability (Di Bella et al ., 2006).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that these pesticides have not been recently used in agriculture after their ban. In all tested samples, the residues were found in the order of DDE > DDD > DDT and this is in agreement with the results of other studies [18,19]. The concentrations of DDTs in investigated samples goby, golden grey mullet and silverside were found lower than those reported by Erdogrul, Ö., 2005 for carp from the Kahramanmaras, Turkey (median 77.4 ng/g ww) [13], and those reported by Covaci, A. et al, 2006 from Danube Delta (2 847 ng/g lipid weight) [18].…”
Section: Ddts Hcb Hcbd Levelssupporting
confidence: 82%
“…The levels of DDTs detected in fish species from the Black Sea, Bulgaria were comparable to those reported for fish from other aquatic ecosystems (Ferreira et al, 2004;Naso et al, 2005;Coelhan et al, 2006;Stoichev et al, 2007;Kalyoncu et al, 2009;Georgieva S., 2012).…”
Section: Source: Authorssupporting
confidence: 77%